Edukasi Kejadian Ikutan Pasca Imunisasi (KIPI) Di Posyandu Desa Cranggang, Kabupaten Kudus Tahun 2024 - Fitrianingsih, Sri; Safitri, Claudia Dinda; Sari, Dessy Erliani Mugita; Hidayati, Rakhmi; Sukarno, Sukarno; Yudanti, Gendis Purno (Muria Jurnal Layanan Masyarakat, 2024)
Immunization is an action in preventing potentially contagious diseases in neonates or children. Immunization needs to be considered to increase the effectiveness and safety of the vaccine to be used. There are various types of immunization, this is followed by the emergence of Post-Immunization Adverse Events (PIAE). PIAE caused can be in the form of mild to severe symptoms. The incident can cause concern for parents and children who want to take immunizations. Activities that can be done before immunization are education related to PIAE so that they don't need to worry. This education about PIAE includes an overview of PIAE, symptoms, causes of PIAE, potential groups of people about PIAE, and steps to take if experiencing PIAE. This health education was carried out at the Posyandu of Cranggang Village, Dawe District, Kudus Regency, Central Java. Media used in education are brochures, and materials delivered directly or face-to-face. The goal is to increase the knowledge of parents and children related to PIAE so that they are not anxious about participating in immunization